2019
DOI: 10.1002/cpt.1378
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Strategies to Measure Medication Adherence via Claims Data in Patients With Chronic Heart Failure

Abstract: Medication adherence correlates with morbidity and mortality in patients with chronic heart failure ( CHF ), but is difficult to assess. We conducted a retrospective methodological cohort study in 3,808 CHF patients, calculating adherence as proportion of days covered ( PDC ) utilizing claims data from 2010 to 2015. We aimed to compare different parameters’ influence on the PDC of elderly CHF pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
(89 reference statements)
0
16
0
Order By: Relevance
“…When interpreting the results of this study, the following limitations need to be considered. The first limitation relates to the data source and calculation of adherence: limitations of data generated for billing purposes are well known 53 and concern, for example, the correctness of the codes. This has been addressed as far as possible by using established and validated code sets to select the population and to define outcomes and covariates (internal validity) and by aligning the study design with previous work (external reference as a surrogate for external validity).…”
Section: Discussionmentioning
confidence: 99%
“…When interpreting the results of this study, the following limitations need to be considered. The first limitation relates to the data source and calculation of adherence: limitations of data generated for billing purposes are well known 53 and concern, for example, the correctness of the codes. This has been addressed as far as possible by using established and validated code sets to select the population and to define outcomes and covariates (internal validity) and by aligning the study design with previous work (external reference as a surrogate for external validity).…”
Section: Discussionmentioning
confidence: 99%
“… 16 Moreover, a previous study showed that different methods of assuming antihypertensive medications’ prescribed daily dose had significant differences on calculating PDC in patients with chronic heart failure using claims data. 35 Further research is warranted to validate these factors. Third, each antihypertensive drug class has a specific indication and regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect measures based on pharmacy records of prescription filling are commonly used (e.g. Hoogendoorn et al, 2019 ; Ihle et al, 2019 ; Simon et al, 2018 ), providing inexpensive but valid and objective adherence information ( Nieuwlaat et al, 2014 ) with good predictive validity (e.g. Choo et al, 1999 ; Steiner & Prochazka, 1997 ) and close correlation with measures based on electric monitoring and pill count ( Choo et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%